Rubus chamaemorus Linnaeus 1753 ... - Jarvis, Charlie (Linnaean Society of London in association with the Natural History Museum, 2007)
Rubus chamaemorus Linnaeus, Species Plantarum 1: 494. 1753. "Habitat in Sueciae paludibus uliginosis, turfosis frequens." RCN: 3767. Lectotype (Chater & al. in Edees & Newton, Brambles Brit. Isles: 16. 1988): Herb. Linn. No. 653.21 (LINN). Current name: Rubus chamaemorus L. (Rosaceae). ... : Published as part of Jarvis, Charlie, 2007, Chapter 7: Linnaean Plant Names and their Types (part R), pp. 785-805 in Order out of Chaos. Linnaean Plant Types and their Types, London :Linnaean Society of London in association with the Natural History Museum on page 801, DOI: 10.5281/zenodo.291971 ...